International research symposium on agricultural greenhouse gas mitigation: From research to implementation: Book of abstracts - Heidecke, Claudia; Clark, Harry; Verchot, Louis; Feike, Til; Grassnick, Nina; Reisinger, Andy; Ringler, Claudia; Runge, Tania; Zhang, Wei (Thünen Institute, 2024)
Total net GHG emissions from Agriculture, Forestry and Other Land Use (AFOLU) averaged around 12.0 GtCO2eq per year during 2007–2016. Approximately 23% of total anthropogenic greenhouse gas emissions derive from AFOLU, while the global food system contributes nearly one third of global greenhouse gas emissions (IPCC 2023). At the same time as being a major emitter, the global food system is called upon to produce approximately 40% more and more diverse foods during 2020 to 2050 to improve the food security, diets and human health of a larger, more urbanized, and better off (but less equal) larger population. With two thirds or more of populations in low- and middle-income countries (LMICs) unable to afford and access healthy diets, there is a particular need to increase production of animal-source foods, fruits and vegetables. At the same time, the productivity of agri-food systems is increasingly impacted by climate change, contributing to a negative feedback loop of climate change induced production expansions that, in turn, fuel climate change.